Immunocytochemical Study of Rabbit-Polyclonal to Mycobacterium Tuberculosis, AB905: Improving Diagnostic of Tuberculous Lymphadenitis - Humairah Medina Liza Lubis; Emni Purwoningsih; Ance Roslina; Muhammad Al Anas (Universitas Muhammadiyah Yogyakarta, 2021)
Tuberculous lymphadenitis (TBLN) is the most common form of extrapulmonary tuberculosis. However, the optimal diagnosis using Fine-Needle Aspiration Cytology (FNAC) or excisional biopsy is uncertain. This research aims to improve the diagnostic of TBLN with FNAC and immunocytochemistry (ICC) compared to the response to antituberculosis therapy. The cross-sectional study involved 43 patients with the criteria for TBLN diagnosis based on the appropriate clinical history of tuberculosis and indicative cytological results. Immunocytochemical examination employed rabbit-polyclonal to Mycobacterium tuberculosis (MTB) antibody (AB905). The MTB expression was found in 35 out of 43 cases (81%) that appropriate cytological features of the tuberculosis process. Meanwhile, eight out of 43 cases (19%) did not express MTB. Diagnostic tests for lesions with a positive cytologic appearance of TBLN and ICC were compared to the response to anti-tuberculosis therapy, revealing the sensitivity, specificity, positive predictive value, and negative predictive value of 95.2%, 75%, 95.2%, and 17%, respectively. Besides, Fisher's exact tests utilized to identify the relationship between two variables; p 0.05 was considered significant. This research found immunocytochemical study was a sensitive and specific tool for improving the diagnostic of TBLN.